Risk factors for heart transplant survival with greater than 5 h of donor heart ischemic time. Issue 8 (20th May 2021) - Tang, Paul C.; Lei, Ienglam; Chen, Y. E.; Wang, Zhong; Ailawadi, Gorav; Romano, Matthew A.; Salvi, Shachi; Aaronson, Keith D.; Si, Ming‐Sing; Pagani, Francis D.; Haft, Jonathan W.
Abstract: Objective: Implantation of donor hearts with prolonged ischemic times is associated with worse survival. We sought to identify risk factors that modulate the effects of prolonged preservation. Methods: Retrospective review of the United Network for Organ Sharing database (2000–2018) to identify transplants with >5 ( n = 1526) or ≤5 h ( n = 35, 733) of donor heart preservation. In transplanted hearts preserved for >5 h, Cox‐proportional hazards identify modifiers for survival. Results: Compared to ≤5 h, transplanted patients with >5 h of preservation spent less time in status 1B (76 ± 160 vs. 85 ± 173 days, p = .027), more commonly had ischemic cardiomyopathy (42.3% vs. 38.3%, p = .002), and less commonly received a blood type O heart (45.4% vs. 50.8%, p < .001). Longer heart preservation time was associated with a higher incidence of postoperative stroke (4.5% vs. 2.5%, p < .001), and dialysis (16.4% vs. 10.6%, p < .001). Prolonged preservation was associated with a greater likelihood of death from primary graft dysfunction (2.8% vs. 1.5%, p < .001) but there was no difference in death from acute (2.0% vs. 1.7%, p = .402) or chronic rejection (2.0% vs. 1.9%, p = .618). In transplanted patients with >5 h of heart preservation, multivariable analysis identified greater mortality with ischemic cardiomyopathy etiology (hazard ratio [HR] = 1.36, p < 0.01), pre‐transplant dialysis (HR = 1.84, p < .01), pre‐transplant extracorporeal membrane oxygenation (ECMO, HR = 2.36, p = .09), and O blood type donor hearts (HR = 1.35, p < .01). Conclusion: Preservation time >5 h is associated with worse survival. This mortality risk is further amplified by preoperative dialysis and ECMO, ischemic cardiomyopathy etiology, and use of O blood type donor hearts.